2020
DOI: 10.3390/ijerph17176248
|View full text |Cite
|
Sign up to set email alerts
|

Barriers Perceived by Managers and Clinical Professionals Related to the Implementation of Clinical Practice Guidelines for Breastfeeding through the Best Practice Spotlight Organization Program

Abstract: International institutions facilitate the contact of health professionals to evidence-based recommendations for promoting exclusive breast feeding (BF). However, the achievement of good rates of exclusive BF is still far from the optimum. The intention of the present work is to determine the barriers identified by managers and health professionals involved in the implementation and sustainability of Clinical Practice Guidelines (CPG) for breastfeeding under the auspices of the Best Practice Spotlight Organizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…In addition, they point out that there is no specific time devoted to BF during the consultation. The role of midwives as facilitators of EBF in Primary Care is essential, as clearly noted by the interviewees in this study and confirmed by other authors [ 21 , 37 , 42 , 55 , 56 , 57 , 58 ] The lack of human resources in Primary Care, thus leading to lack of time for health professionals, implies that midwives must take extra time from their daily consultation to help women with EBF [ 39 , 59 ].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…In addition, they point out that there is no specific time devoted to BF during the consultation. The role of midwives as facilitators of EBF in Primary Care is essential, as clearly noted by the interviewees in this study and confirmed by other authors [ 21 , 37 , 42 , 55 , 56 , 57 , 58 ] The lack of human resources in Primary Care, thus leading to lack of time for health professionals, implies that midwives must take extra time from their daily consultation to help women with EBF [ 39 , 59 ].…”
Section: Discussionsupporting
confidence: 76%
“…Taking into account the results of our study, the lack of investment by institutions in measures to enhance EBF and the absence of laws to protect it, mean that its promotion and support remain exclusively in the hands of health professionals and their willingness to spend time on this matter. Training in BF depends on the will of health professionals themselves who are often not motivated to promote EBF due again to the lack of resources, time and support from the institutions themselves, as previously observed in other studies [59,[63][64][65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“… 32 Budget cuts and lack of support from administrators impact staffing rations for LEs and have direct consequences for service delivery. 37 , 38 Stable and good-sized professional staff is indispensable for the implementation and promotion of evidenced-based practices related to breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…(51) El progreso en la ciencia de la implementación sus teorías y marcos son esenciales para identificar problemas clínicos, diseñar estrategias, implementar cambios, evaluar resultados e identificar factores que afectan la sostenibilidad de las intervenciones. (52,53) La identificación de barreras en la aplicación de las GBP tiene implicaciones directas para los profesionales de enfermería, quienes deben superar la resistencia al cambio, abordar actitudes negativas y vencer desafíos identificados.…”
Section: Barreras Para La Implementaciónunclassified